Highly sensitive piezotronic pressure sensors based on undoped GaAs nanowire ensembles. (6th June 2019) - Calahorra, Yonatan; Husmann, Anke; Bourdelain, Alice; Kim, Wonjong; Vukajlovic-Plestina, Jelena; Boughey, Chess; Jing, Qingshen; Fontcuberta i Morral, Anna; Kar-Narayan, Sohini
Abstract: Semiconducting piezoelectric materials have attracted considerable interest due to their central role in the emerging field of piezotronics, where the development of a piezo-potential in response to stress or strain can be used to tune the band structure of the semiconductor, and hence its electronic properties. This coupling between piezoelectricity and semiconducting properties can be readily exploited for force or pressure sensing using nanowires, where the geometry and unclamped nature of nanowires render them particularly sensitive to small forces. At the same time, piezoelectricity is known to manifest more strongly in nanowires of certain semiconductors. Here, we report the design and fabrication of highly sensitive piezotronic pressure sensors based on GaAs nanowire ensemble sandwiched between two electrodes in a back-to-back diode configuration. We analyse the current–voltage characteristics of these nanowire-based devices in response to mechanical loading in light of the corresponding changes to the device band structure. We observe a high piezotronic sensitivity to pressure, of 7800 meV MPa −1 . We attribute this high sensitivity to the nanowires being fully depleted due to the lack of doping, as well as due to geometrical pressure focusing and current funnelling through polar interfaces.